The Strategy of Islamic Religious Teachers in the Development of Akhlakul Karimah in Integrated Islamic Elementary School Students - Imaduddin Imaduddin; Sodikin Sodikin; Zainal Abidin (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
Study This discuss (1) role strategy Teacher education religion Islam in coaching morals karimah; (2) form coaching Akhlakul Karimah conducted by Islamic religious education teachers. Study This using a descriptive qualitative approach. The results of the study are (1) strategy Teacher education religion Islam in coaching morals karimah done through habituation, exemplary, recommendation or advice, prohibition, supervision and punishment; (2) moral development in SDIT Permata Kota Probolinggo is divided become two that is intracurricular Which focused on religious studies consisting of Aqidah/Tawhid, and extracurricular activities , including sports, field trips, and social activities; And form coaching morals done with read prayer read Al-Qur'an, Salat Zhuhur And commemorate day Big Islam like Year new And Mawlid Prophet.